São Paulo em noite de festa: experiências culturais dos migrantes nordestinos (1940-1990) - Paes, Jurema Mascarenhas (2009)
In this thesis, the experiences and cultural translations of the northeastern migrants are analyzed in their processes of miscegenation by means of music, dance and the sociability spaces, in the second half of the 20th century (decades of 1950 to 1990), in the city of São Paulo. The successful trajectory of the artist Luiz Gonzaga is observed, by means of the creation of the baião music and music genre, the instrumental formation of the northeastern trio and all his vocal and scenic speech, representative of the Northeastern region, which occurred in the in-between field-city. The emersion of Luiz Gonzaga is articulated with the migratory flow of the 1950s, with highlights for the city of São Paulo and its work and growth speech. In sequence, the 1960s are focused, with the emersion of the Pedro Sertanejo forró house, one of the first in the city of São Paulo, and of the recording studio Cantagalo , unfolding the whole social network of knowledge and power, observing that the cultural manifestations, in their day-to-day social processes, worked as fighting strategies for territories inside the city. This is a thesis prepared under the perspective of Cultural History, permeating the experiences and strategies, ways of life, of expressing and of living, the miscegenation processes, diverse organization manners, watching for shared and confronted social experiences, analyzing symbols, images, mentalities, cultural practices, as experiences of power, domination, resistance, fight, negotiation, aesthetic and social conflicts. For such, it is sought to work in the intersection of the happenings and in the articulation of the differences between migration, field and city, popular culture and cultural industry, History and music, Oral History, photography and memory, day-to-day and culture, all of this to better understand the imbrications of the half-breed amalgams of the northeastern culture in the city of São Paulo while processes of negotiations and social conflicts